17. CLINICAL, SUBCLINICAL CHARACTERISTICS AND RESULTS OF TREATMENT OF COVID-19 IN PREGNANT WOMEN AT THE NATIONAL HOSPITAL OF TROPICAL DISEASES (Vietnam Journal of Community Medicine, 2024)
Objective: Describe clinical features, paraclinical characteristics and treatment results of COVID-19 in pregnant women treated at the National Hospital of Tropical Diseases in 2020-2022. Subject and method: A cross-sectional study was carried out in the medical record of 209 pregnant women with COVID-19 who were diagnosed with COVID-19 by RT-PCR-SARS-CoV-2 test, admitted to the National Hospital for Tropical Diseases from January 1, 2020 to June 30, 2022. Results: Common symptoms of COVID-19 disease in Pregnant women are: cough (82.3%) and fever (67.5%). Abnormal subclinical features of COVID-19 in Pregnant women are: anemia (34.5%), lymphopenia (51.7%), increased D-dimer (94.7%), increased fibrinogen (59.7%), increased CRP (78%), elevated LDH (40.3%). Outcomes of pregnant women: the mortality rate was 2.9%. Pregnancy outcomes: 35.4% (74/209) of pregnant women need to terminate pregnancy, 85.1% (63/74) terminate during preterm pregnancy. Conclusion: Common symptoms of COVID-19 in Pregnant women are cough and fever. COVID-19 disease in pregnant women has the intention of increasing D-dimer, fibrinogen, CRP, LDH and lymphopenia, decreasing hemoglobin. Pregnant women with COVID-19 have a high rate of severe illness but the death rate is not high. Pregnant women with COVID-19 tend to need early cesarean sections.
Keywords: COVID-19, Pregnant women, results of treatment.